1989
DOI: 10.1017/s0031182000062211
|View full text |Cite
|
Sign up to set email alerts
|

Action of cyclosporin A on the tapewormsHymenolepis microstoma, H. diminutaandMesocestoides corti in vivo

Abstract: The in vivo activity of two cyclosporins, cyclosporin A (CsA) and a non-immunosuppressive derivative of dihydrocylosporin A (DHCsA-d) against three tapeworms, Hymenolepis microstoma, H. diminuta and Mesocestoides corti, has been assessed. CsA reversibly reduced the dry weight of H. microstoma in the mouse, briefly delayed oviposition and had a statistically significant effect on worm numbers recovered. Oral and subcutaneous treatments of both CsA and DHCsA-d were effective in reducing worm weight; juvenile wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…E/S products from N. brasiliensis and Ascaris suum are resistant to rMCP-I (from rat connective tissue mast cells) and to rMCP-II (from rat IMMC) (Qureshi et al 1987) but internal cuticular collagens from Necator americanus are degraded by rMCP-II (McKean & Pritchard 1989). The biomass of H. microstoma decreased immediately following administration of CsA but, as demonstrated elsewhere (Chappell et al 1989), rose again after drug withdrawal. Here CsA had no effect on mucosal mastocytosis and mMCP-I concentration in the intestine, bile duct or serum since the drug dose was essentially nonimmunosuppressive.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…E/S products from N. brasiliensis and Ascaris suum are resistant to rMCP-I (from rat connective tissue mast cells) and to rMCP-II (from rat IMMC) (Qureshi et al 1987) but internal cuticular collagens from Necator americanus are degraded by rMCP-II (McKean & Pritchard 1989). The biomass of H. microstoma decreased immediately following administration of CsA but, as demonstrated elsewhere (Chappell et al 1989), rose again after drug withdrawal. Here CsA had no effect on mucosal mastocytosis and mMCP-I concentration in the intestine, bile duct or serum since the drug dose was essentially nonimmunosuppressive.…”
Section: Discussionsupporting
confidence: 56%
“…CsA is not toxic to H. diminuta in vivo or in vitro (Chappell et al 1989, Wastling et el. 1990) and immunosuppressive doses allow > 90% of worms to survive to maturity in mice, delaying but not completely abrogating worm expulsion (Wastling et al 1990, present study).…”
Section: Discussionmentioning
confidence: 95%
“…The structural integrity of the worm is ultimately compromised by surface damage around the dorsal tubercles or the protrusion of the gut through the tegument (Munro & McLaren 1990a, Millership 1995. However, it seems unlikely that the gut is the primary target for CsA since the drug is active against cestodes which lack an alimentary canal (Chappell, Wastling & Hurd 1989). This study offers further evidence of the involvement of the immune system with drug action using CsA, a drug which is both immunosuppressive and selectively antiparasitic.…”
Section: Discussionmentioning
confidence: 70%
“…For instance, Munro et al (1991) showed that CsA treatment severely limits the migration of recently penetrated schistosomula; it is possible that these immobilized larvae are killed by immune effectors but there is currently no firm evidence to support this contention. What remains to be explained, therefore, is why CsA is selectively toxic and fails to damage the tegument of certain helminth parasites such as Hymenolepis diminuta (Chappell, Wastling & Hurd 1989). Recent studies suggest that cyclophilins are present in parasites and these may be the endogenous targets for the action of CsA (Roberts, Sternberg & Chappell 1995) although further data are required before such proposals can be substantiated.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other cestode larvae, against which mebendazole exerts a parasitostatic effect only. Deleterious actions of other drugs on Mesocestoides tetrathyridia, including cyclosporin A (Chappell et al 1989) and albendazole (Terenina et al 1998), have also been reported.…”
Section: Relevance Of Echinococcus Metacestode Screening Models For Omentioning
confidence: 99%